ANALISIS BUTIR SOAL MATEMATIKA MATERI TRANSFORMASI BERBASIS GEOGEBRA DI SMPN 3 SUWAWA - Wahyuni Paneo; Tedy Machmud; Majid Majid (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2025)
This study aims to analyze mathematics test items on the topic of transformations conducted at SMP Negeri 3 Suwawa for grade IX students. The research sample consisted of 30 students. The instrument used was an essay test comprising 10 questions. The research employed a quantitative descriptive method. The results of the analysis showed that out of the 10 questions, 60% were valid while 40% were invalid. The reliability coefficient obtained was 0.6945, indicating that the test was reliable. Therefore, it can be concluded that the overall quality of the test items falls into the high category.